2010
DOI: 10.4103/0972-2327.74190
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, electrophysiologic, and histopathologic profile, and outcome in idiopathic inflammatory myositis: An analysis of 68 cases

Abstract: Objectives:To study the electroclinical and histopathologic profile of idiopathic inflammatory myositis (IIM) with reference to prognosis and survival rate.Materials and Methods:Diagnosis of IIM was based on the Bohan and Peter criteria. Patients who improved and those whose condition worsened or who expired due to IIM per se at last follow-up were classified to have favorable and poor outcomes, respectively. Fisher’s exact test was used for univariate analysis of prognostic factors.Results:The study cohort co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
3
8
2
Order By: Relevance
“…31 Another Indian Cohort by Ramesha et al have described a medication free remission in 39/68 (57%) of their cohort, however their cohort size is much smaller with lesser duration of follow-up. 35 Treatment free remission in our cohort was 13.8%; it was associated with longer duration of followup, absence of baseline dysphagia and Ro52 positivity. Treatment free remission is a subset which needs a dedicated study in future prospective cohorts.…”
Section: Discussionmentioning
confidence: 53%
“…31 Another Indian Cohort by Ramesha et al have described a medication free remission in 39/68 (57%) of their cohort, however their cohort size is much smaller with lesser duration of follow-up. 35 Treatment free remission in our cohort was 13.8%; it was associated with longer duration of followup, absence of baseline dysphagia and Ro52 positivity. Treatment free remission is a subset which needs a dedicated study in future prospective cohorts.…”
Section: Discussionmentioning
confidence: 53%
“…4 From India, Ramesh et al reported 70% of their patients were in remission which they have termed as a favorable outcome, while 57% were off medication termed as an excellent outcome. 11 We could not find any baseline factors predicting inactive disease or good response. Few studies had additionally reported the predictors of the patient's good response to the treatment, such as duration of illness less than 6 months, absence of cardiac involvement, 4,11 age less than 60 years, and absence of dysphagia.…”
Section: Discussionmentioning
confidence: 78%
“…4,5,7,10 Indian data focusing on cohort-based long-term outcomes such as remission status, muscle strength regaining, and damage accumulation are limited. 11,12 The validated tools were not used in either of the studies for measuring the outcome of this patient group. In contrast, significant data are available on the outcome of the juvenile form of dermatomyositis.…”
Section: Introductionmentioning
confidence: 99%
“…To date there are not many studies reported in the literature of scleroderma-myositis overlap. Most of them are limited to a small number of overlap cases [ 4 , 25 28 ]. The comparison of our data with the results of other workgroups is challenging, since despite the definitions of overlap syndromes being obvious, sometimes it is not clear, whether myositis is represented as muscle involvement of SSc or as a different disease.…”
Section: Discussionmentioning
confidence: 99%